Cut and thrust [compact disc, unabridged] - Woods, Stuart (Woods, Stuart. Stone Barrington novel., 2014)
Stone Barrington has traveled to Los Angeles for the Democratic National Convention and finds that the political scene has been shaken up. First Lady Katherine Rule Lee is running for the party nomination, a loyal senator has died and left her seat vacant, and the Secret Service has received a credible threat toward Kate. It will take all of Stone's discretion and powers of persuasion to help arrange things for a desirable outcome.